Methanation catalyst for methanation of carbon dioxide and production method therefor, and method for methanation of carbon dioxide
Patent Information
- Application Number
- JP2023129458
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025023000001 
Figure 2025025023000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a methanation catalyst for methanating carbon dioxide, a method for producing the same, and a method for producing methane using the methanation catalyst for methanating carbon dioxide. [Background technology]
[0002] Methane, which is expected to be a new energy source, can also be obtained by methanating carbon dioxide. However, currently, catalysts carrying precious metal elements are generally used in the production of methane from carbon dioxide gas, making the system very expensive. In particular, the price of the catalyst accounts for the majority of the cost of the entire methane production system.
[0003] In other words, the spread of the system will be promoted by realizing lower prices as well as further improving the performance of catalysts. Therefore, there is a strong demand to switch from catalysts that use large amounts of precious metal elements to catalysts that use less expensive elements in as small amounts as possible.
[0004] Furthermore, it is desirable for the catalyst to be reusable multiple times, and therefore the catalyst is required to have sufficient strength so that sufficient catalytic activity can be obtained even after repeated use. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2022-94211 Summary of the Invention [Problem to be solved by the invention]
[0006] The methanation catalyst for methanating carbon dioxide disclosed in the above-mentioned Patent Document 1 supports one or more promoters selected from the group consisting of lanthanum oxide, yttrium oxide, and praseodymium oxide, and therefore cannot be said to be an inexpensive, industrially applicable catalyst. [Means for solving the problem]
[0007] The above technical problems can be solved by the present invention as follows.
[0008] That is, the present invention provides a methanation catalyst for methanating carbon dioxide, which contains at least magnesium, aluminum and nickel, the magnesium and aluminum being in the form of a composite oxide, the nickel being metallic nickel, and containing 10 to 50 wt% magnesium, 5 to 35 wt% aluminum and 1 to 30 wt% nickel (Invention 1).
[0009] The present invention also relates to the methanation catalyst for methanating carbon dioxide according to Invention 1, wherein the average particle size of the metallic nickel in the catalyst is 1 to 50 nm. (Invention 2)
[0010] The present invention also relates to a methanation catalyst for methanating carbon dioxide according to Invention 1, wherein the BET specific surface area of the catalyst is 5 to 100 m 2 / g of carbon dioxide is methanated. (Invention 3)
[0011] The present invention also relates to a methanation catalyst for methanating carbon dioxide according to Invention 1, which contains one or more metals selected from gold, silver, platinum, palladium, ruthenium, cobalt, iron, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, and titanium, each having an average particle size of 50 nm or less. (Invention 4)
[0012] The present invention also provides a methanation catalyst for methanating carbon dioxide according to Invention 1, wherein the average crushing strength of the catalyst is 3 kgf / cm 2The above is a methanation catalyst for methanating carbon dioxide. (Invention 5)
[0013] The present invention also relates to a method for methanating carbon dioxide using the methanation catalyst for methanating carbon dioxide described in Invention 1. (Invention 6)
[0014] A method for producing methane by reacting carbon dioxide in the presence of the methanation catalyst for methanating carbon dioxide according to Invention 1. (Invention 7)
[0015] The present invention also relates to a method for producing a methanation catalyst for methanating carbon dioxide according to Invention 1, which comprises producing hydrotalcite particles containing constituent elements as a precursor by a coprecipitation reaction, forming a molded body, heating and sintering the body to form a porous catalyst body, and then heating and reducing the body. (Invention 8) Effect of the Invention
[0016] The methanation catalyst for methanating carbon dioxide according to the present invention is a catalyst for producing methane from carbon dioxide, and is capable of methanating carbon dioxide even in a temperature range of 300° C. or less. Furthermore, it is a high-strength methanation catalyst capable of methanating carbon dioxide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The configuration of the present invention will be described in detail as follows.
[0018] First, the methanation catalyst for methanating carbon dioxide according to the present invention will be described.
[0019] The methanation catalyst for methanating carbon dioxide according to the present invention contains at least magnesium, aluminum and nickel, the magnesium and aluminum being a composite oxide, the nickel being metallic nickel, and containing 10 to 50 wt% magnesium, 5 to 35 wt% aluminum and 1 to 30 wt% nickel. In addition to magnesium, aluminum and nickel, elements such as sodium, silicon and zinc may be contained, but are not limited thereto. If calcium is contained, there is a risk that the catalyst will not have the desired strength, so it is preferable to configure the catalyst without containing calcium.
[0020] The magnesium content of the methanation catalyst for methanating carbon dioxide according to the present invention is 10 to 50 wt% based on the catalyst. If the magnesium content is less than 10 wt%, the BET specific surface area of the catalyst becomes small and the catalyst becomes less porous, which may reduce the probability of contact with gas, and furthermore, the resistance to sulfur poisoning is also reduced. If the magnesium content exceeds 50 wt%, the mechanical strength is reduced. The magnesium content is preferably 15 to 45 wt%, more preferably 20 to 40 wt%.
[0021] The aluminum content of the methanation catalyst for methanating carbon dioxide according to the present invention is 5 to 35 wt% relative to the catalyst. If the aluminum content is less than 5 wt%, the mechanical strength is reduced. If the aluminum content exceeds 35 wt%, the BET specific surface area is reduced and the catalyst is no longer porous, which may reduce the probability of contact with gas. The aluminum content is more preferably 6 to 30 wt%, and even more preferably 7 to 25 wt%.
[0022] The magnesium and aluminum in the methanation catalyst for methanating carbon dioxide according to the present invention may be contained in the catalyst in the form of a composite oxide. The methanation catalyst for methanating carbon dioxide according to the present invention is formed by subjecting an oxide containing magnesium, aluminum, and nickel, such as a periclase structure or a spinel structure, to a reduction heat treatment in which only the nickel component is precipitated as fine particle-shaped metallic nickel from the oxide containing magnesium and aluminum, thereby containing nickel metal on the surface and / or pore surfaces of the oxide containing magnesium and aluminum.
[0023] The nickel content of the methanation catalyst for methanating carbon dioxide according to the present invention is 1 to 30 wt% relative to the catalyst. If the nickel content is less than 1 wt%, sufficient catalytic activity may not be obtained, and the carbon dioxide conversion rate, which means the efficiency of methanating a mixed gas of carbon dioxide and hydrogen, may decrease. If the nickel content exceeds 30 wt%, the particle size of the metallic nickel fine particles exceeds 50 nm and grows large, so that sufficient catalytic activity may not be obtained, and the carbon dioxide conversion rate may decrease, or the catalytic activity temperature may become high. In consideration of economic efficiency, it is preferable that the nickel amount is small within the range of the content that provides sufficient catalytic activity. The nickel content is more preferably 5 to 25 wt%, and even more preferably 10 to 20 wt%.
[0024] The nickel content (Ni / (Mg+Al+Ni)) of the methanation catalyst for methanating carbon dioxide according to the present invention is preferably 0.05 to 0.55 (molar ratio) relative to the total amount of Mg, Al and Ni.
[0025] The ratio of magnesium to aluminum in the methanation catalyst for methanating carbon dioxide according to the present invention is not particularly limited, but the more magnesium relative to aluminum, the more preferable, and the molar ratio of magnesium to aluminum is more preferably Mg:Al=5:1 to 1:1. If the magnesium exceeds the above range, it becomes difficult to easily obtain a molded body having sufficient strength, and if it is below the above range, it becomes difficult to obtain the characteristics of a porous carrier.
[0026] The average particle size of metallic nickel contained in the methanation catalyst for methanating carbon dioxide according to the present invention is preferably 1 to 50 nm. Outside this range, there is a risk that sufficient catalytic activity will not be obtained. The average particle size of metallic nickel contained in the catalyst is more preferably 5 to 40 nm, and further preferably 8 to 30 nm.
[0027] The methanation catalyst for methanating carbon dioxide according to the present invention is one in which metallic nickel is present in a composite oxide containing magnesium and aluminum. The metallic nickel in the methanation catalyst for methanating carbon dioxide according to the present invention is preferably present in the vicinity of the surface of the particles constituting the catalyst. The methanation catalyst for methanating carbon dioxide according to the present invention is preferably used in the form of a granulated molded body, and the metallic nickel may be present in the vicinity of the surface of the molded body. The methanation catalyst for methanating carbon dioxide according to the present invention contains metallic nickel in the form of very fine particles. Therefore, the area in which metallic nickel, which is an active metal species, comes into contact with carbon dioxide is increased, making it possible to methanate a mixed gas of carbon dioxide and hydrogen, and thus having excellent catalytic activity.
[0028] The BET specific surface area of the methanation catalyst for methanating carbon dioxide according to the present invention is 5 to 100 m 2 / g is preferred. BET specific surface area is 5m 2 If the BET specific surface area is less than 100 m / g, the pore size becomes too large and there is a risk that the active metal species cannot be sufficiently dispersed and supported. 2 If the thickness exceeds 15 to 80 mm / g, sufficient strength may not be obtained. 2 / g, more preferably 20 to 60m 2 / g.
[0029] The methanation catalyst for methanating carbon dioxide according to the present invention may support other metals in addition to nickel. By supporting other metals as active metal species on the methanation catalyst for methanating carbon dioxide according to the present invention, higher catalytic activity can be expected.
[0030] The supported metal in the present invention is not particularly limited, and may be a noble metal element or a base metal element. Examples of supported metals include gold, silver, platinum, palladium, ruthenium, cobalt, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, titanium, and iron, and may be used alone or in combination of two or more. The supported metal may be simultaneously contained in the porous catalyst body when it is produced, or may be supported after the porous catalyst body is produced, and is not particularly limited. The supporting method is also not particularly limited, and may be a commonly used method such as a spray drying method or an impregnation method.
[0031] The average particle size of the supported metal in the present invention is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less. If the average particle size of the supported metal exceeds 50 nm, there is a risk that the supporting effect cannot be obtained. The lower limit of the average particle size of the supported metal is not particularly limited, but is preferably about 0.5 nm. By including the supported metal, the catalytic activity in a relatively low temperature range of 300 ° C or less can be further improved.
[0032] The supported metal in the present invention is preferably contained since it becomes an active metal species, and the preferred content is about 0.01 to 10 wt% of the catalyst. If it is less than 0.01 wt%, sufficient carbon dioxide methanation properties cannot be obtained, and if it exceeds 10 wt%, the cost increases, which is not industrially preferred.
[0033] The methanation catalyst for methanating carbon dioxide according to the present invention can be made into a molded body. The shape and size are not particularly limited, and may be, for example, various shapes such as spherical, cylindrical, tubular, and pellet, or may be applied to a honeycomb body. In general, the size of a catalyst having a spherical, cylindrical, or tubular shape is about 0.1 to 30 mm, and a spherical shape is preferable from the viewpoint of packing into a column, etc. The molded body of the methanation catalyst for methanating carbon dioxide may be adjusted in strength and pore distribution density by adding various binders such as organic and inorganic substances.
[0034] The average crushing strength of the methanation catalyst for methanating carbon dioxide according to the present invention is 3 kgf / cm 2 More than 3kgf / cm is preferable. 2 If the average crushing strength is less than this, it may be crushed by external stress or expansion and contraction due to repeated use, resulting in a risk of not being able to obtain the desired catalytic activity, or of cracking during use at high temperatures, or of destruction or powdering when coking occurs inside. The average crushing strength is more preferably 4 to 50 kgf / cm 2 , and more preferably 5 to 40 kgf / cm 2 It is.
[0035] The pore volume of the methanation catalyst for methanating carbon dioxide according to the present invention is 0.01 to 0.50 cm 3 / g is preferred. 3 If the surface area is less than 0.50 cm3 / g, nickel and other supported metals may not be sufficiently dispersed and supported. 3 If the pore volume exceeds 0.02 to 0.45 cm3 / g, the mechanical strength may be weakened. 3 / g, and more preferably 0.05 to 0.40 cm 3 / g.
[0036] The methanation catalyst for methanation of carbon dioxide according to the present invention has a high average crushing strength, and therefore can maintain the same carbon dioxide conversion rate as that at the first use even when used repeatedly multiple times, i.e., has excellent cycle characteristics. The methanation catalyst for methanation of carbon dioxide according to the present invention not only exhibits a high carbon dioxide conversion rate in a relatively low temperature range of 300°C or less, but can also be used repeatedly, and is therefore environmentally and economically excellent. Furthermore, the methanation catalyst for methanation of carbon dioxide according to the present invention has excellent strength, and therefore there is little risk of the shape or catalytic activity changing even when it is packed into a column or the like for use, and is therefore industrially preferable.
[0037] Next, a method for producing the methanation catalyst for methanating carbon dioxide according to the present invention will be described.
[0038] The method for producing the methanation catalyst for methanating carbon dioxide according to the present invention is not particularly limited, but it is preferable to produce the catalyst by producing hydrotalcite particles containing the constituent elements as a precursor by a coprecipitation reaction, preparing a molded body, heating and sintering the molded body to form a porous catalyst body, and then heating and reducing the same.
[0039] The hydrotalcite particles containing magnesium, aluminum and nickel in the present invention are preferably obtained by mixing an anion-containing alkaline aqueous solution with an aqueous solution of a magnesium raw material, an aluminum raw material and a nickel raw material to obtain a mixed solution having a pH value in the range of 7.0 to 13.0, aging the mixed solution in the temperature range of 50 to 300°C, and then filtering and separating the resultant mixture, followed by drying.
[0040] The maturation time in the first stage is not particularly limited, but is preferably 1 to 80 hours, more preferably 3 to 24 hours, and further preferably 5 to 18 hours. A growth reaction for more than 80 hours is not industrially feasible.
[0041] The magnesium, aluminum, and nickel raw materials are not particularly limited as long as they are water-soluble, such as nitrates.
[0042] As the magnesium raw material, magnesium oxide, magnesium hydroxide, magnesium oxalate, magnesium sulfate, magnesium sulfite, magnesium nitrate, magnesium chloride, magnesium citrate, basic magnesium carbonate, magnesium benzoate, etc. can be used.
[0043] As the aluminum source, aluminum oxide, aluminum hydroxide, aluminum acetate, aluminum chloride, aluminum nitrate, aluminum oxalate, basic ammonium aluminum, etc. can be used.
[0044] As the nickel salt raw material, nickel oxide, nickel hydroxide, nickel sulfate, nickel carbonate, nickel nitrate, nickel chloride, nickel benzoate, basic nickel carbonate, nickel formate, nickel citrate, diammonium nickel sulfate, etc. can be used.
[0045] In addition, various methods can be used as a method for supporting nickel contained in the methanation catalyst for methanating carbon dioxide according to the present invention. For example, there is a method in which nickel is supported on a porous catalyst body containing magnesium and aluminum by a normal precipitation method, a heat impregnation method, a room temperature impregnation method, a vacuum impregnation method, an equilibrium adsorption method, an evaporation to dryness method, a competitive adsorption method, an ion exchange method, a spray method, a coating method, or the like, or a method in which nickel is dissolved as a spinel crystal structure compound containing magnesium and aluminum, and metallic nickel is precipitated on a spinel support containing magnesium and aluminum by heat treatment.
[0046] Also, a method is known in which hydrotalcite particles are calcined to obtain composite oxide particles, and then the composite oxide particles are hydrated with an anion-containing aqueous solution to obtain layered double hydroxide particles. In the present invention, nickel may be contained by the following production method. The nickel-containing hydrotalcite particles may be calcined by heating as necessary, and then reduced by heating.
[0047] That is, the porous catalyst body in the present invention may support active metal species by using a method in which a methanation catalyst for methanating carbon dioxide or a hydrotalcite phase containing nickel is regenerated in the vicinity of the surface of the molded body by impregnating the porous catalyst body in a solution containing nickel.
[0048] The average plate surface diameter of the hydrotalcite particles containing magnesium, aluminum and nickel in the present invention is preferably 0.05 to 0.4 μm. If the average plate surface diameter is less than 0.05 μm, filtration and washing with water become difficult, making industrial production difficult, and if it exceeds 0.4 μm, it is difficult to prepare a porous catalyst body.
[0049] The crystallite size D006 of the hydrotalcite particles in the present invention is preferably 0.001 to 0.08 μm. If the crystallite size D006 is less than 0.001 μm, the viscosity of the aqueous suspension is very high, making industrial production difficult, and if it exceeds 0.08 μm, it is difficult to prepare a porous catalyst body. The crystallite size D006 is more preferably 0.002 to 0.07 μm.
[0050] The BET specific surface area of the hydrotalcite particles containing magnesium, aluminum and nickel in the present invention is 3.0 to 300 m 2 / g is preferable. 2 If the average particle size is less than 300 m / g, it is difficult to prepare a porous catalyst body. 2 If it exceeds 10 ... 2 / g is more preferred.
[0051] In the present invention, the ratio of magnesium to aluminum in the hydrotalcite containing magnesium and aluminum is not particularly limited, but the molar ratio of magnesium to aluminum is more preferably Mg:Al=4:1 to 1:1.
[0052] The secondary agglomerated particle diameter of the hydrotalcite particles in the present invention is preferably 0.1 to 200 μm. If the secondary agglomerated particle diameter of the hydrotalcite particles is less than 0.1 μm, the pulverization process becomes difficult, making industrial production difficult, and if it exceeds 200 μm, it is difficult to prepare a molded body. The secondary agglomerated particle diameter of the hydrotalcite particles is more preferably 0.2 to 100 μm.
[0053] The pulverization process can be carried out using a general pulverizing device (such as an atomizer, a yariya, or a Henschel mixer).
[0054] The molded body in the present invention is preferably prepared by adding a molding aid, a binder, and further water and alcohol or a combustible substance as a dispersion medium to the hydrotalcite particles containing at least magnesium, aluminum, and nickel as necessary, kneading the mixture into a clay-like mixture in a kneading machine (screw kneader, etc.), and then molding the mixture. Methods for molding that can be used include compression molding, press molding, tablet molding, etc.
[0055] The molded body in the present invention is not particularly limited, and may have any shape that is commonly used for catalysts. Examples of the shape of the molded body include a sphere, a cylinder, a hollow cylinder, and a pellet.
[0056] When the molded article in the present invention is spherical, the size of the molded article is preferably 0.5 to 30 mmφ, more preferably 1 to 10 mmφ, and further preferably 2 to 8 mmφ.
[0057] The molding aid in the present invention may be a composition containing fatty acid, cellulose, polyvinyl alcohol, starch, methyl cellulose, maltose, carboxymethyl cellulose, etc., and two or more of them may be used in combination. The molding aid is burned and eliminated by the firing treatment and does not remain in the porous catalyst body. The amount of the molding aid to be added is preferably, for example, 1 to 50 parts by weight based on 100 parts by weight of the hydrotalcite particles containing magnesium, aluminum, and nickel.
[0058] The binder in the present invention may be a composition containing non-rehydratable alumina, α-alumina, aluminum salt, silica, clay, talc, bentonite, zeolite, cordierite, titania alkali metal salt, alkaline earth metal salt, rare earth metal salt, zirconia, mullite, sepiolite, montmorillonite, halloysite, saporite, stevensite, hectorite, silica alumina, etc., and two or more of them may be used in combination. When a salt other than an oxide is added, it is important that the salt is decomposed to an oxide by firing. The amount of addition is preferably, for example, 1 to 50 parts by weight based on 100 parts by weight of hydrotalcite particles containing magnesium and aluminum.
[0059] Examples of the alcohols that can be used in the present invention include monohydric alcohols such as ethanol and propanol, glycols such as ethylene glycol, propylene glycol, butanediol and polyethylene glycol, and polyhydric alcohols such as glycerin, and two or more of these may be used in combination. The amount of the alcohol added is preferably, for example, 50 to 150 parts by weight per 100 parts by weight of the hydrotalcite particles containing magnesium and aluminum.
[0060] In addition, as the combustible material in the present invention, wood chips, cork grains, coal powder, activated carbon, crystalline cellulose powder, starch, sucrose, gluconic acid, polyethylene glycol, polyvinyl alcohol, polyacrylamide, polyethylene, polystyrene, etc., and mixtures thereof may be added. The more the amount of the combustible material added, the larger the pore volume becomes, but adding too much of the material causes a decrease in strength, so the amount added can be adjusted taking the strength into consideration.
[0061] When a honeycomb shape is to be formed, a method may be freely selected according to need.
[0062] The molded product molded by the above method can be dried by natural drying, hot air drying, vacuum drying, or the like.
[0063] Furthermore, the porous catalyst body of the present invention can be obtained by heat-treating the molded body. The heat treatment temperature is preferably 700°C to 1500°C. If the heat treatment temperature is less than 700°C, a long period of heat treatment is required to maintain the crushing strength, which is not industrially feasible. If the heat treatment temperature exceeds 1500°C, the pores of the porous catalyst body may be crushed. The heat treatment temperature is more preferably 800°C to 1400°C, and further preferably 900°C to 1300°C.
[0064] The heat treatment time is preferably 1 to 72 hours. If the heat treatment time is less than 1 hour, the crushing strength decreases, and if it exceeds 72 hours, the pores of the porous catalyst body are crushed, and a long heat treatment is not industrially practical. The heat treatment time is more preferably 2 to 60 hours, and further preferably 3 to 50 hours.
[0065] The methanation catalyst for methanating carbon dioxide according to the present invention is obtained by subjecting the porous catalyst body to a reduction treatment. The reduction temperature is preferably 700°C to 1000°C. If the reduction temperature is less than 700°C, nickel is not metallized, and there is a risk that the catalytic activity aimed at by the present invention cannot be obtained. If the reduction temperature exceeds 1000°C, sintering of nickel progresses and the particle size of the metallic nickel fine particles becomes large, so that the rate of methanation of carbon dioxide at low temperatures decreases, and further, the coking resistance may also decrease. The reduction temperature is more preferably 750 to 950°C. The atmosphere during reduction is not particularly limited as long as it is a reducing atmosphere such as a gas containing hydrogen. The reduction treatment time is not particularly limited, but is preferably 0.5 to 24 hours. If it exceeds 24 hours, no industrial merit is found. The reduction treatment time is more preferably 1 to 10 hours.
[0066] Next, a method for producing methane using the methanation catalyst according to the present invention for methanating carbon dioxide will be described.
[0067] The methanation catalyst for methanating carbon dioxide according to the present invention can obtain a gas containing methane by contacting it with a gas containing carbon dioxide and hydrogen.
[0068] The method for methanating carbon dioxide using the methanation catalyst of the present invention for methanating carbon dioxide is not particularly limited as long as the method involves contacting a gas containing carbon dioxide with the methanation catalyst of the present invention for methanating carbon dioxide in a temperature range (reaction temperature) in which the catalyst has catalytic activity.
[0069] The reaction temperature of the methanation catalyst for methanating carbon dioxide according to the present invention is preferably 150°C to 600°C, more preferably 200°C to 500°C, and further preferably 250°C to 400°C. If the reaction temperature is less than 150°C, sufficient catalytic activity for methanating carbon dioxide may not be obtained, and the carbon dioxide conversion rate may be low. In addition, since methanation is an exothermic reaction, if the reaction temperature exceeds 600°C, the carbon dioxide conversion rate may be reduced.
[0070] The carbon dioxide used in the present invention is not particularly limited, and the purity is also not particularly limited, and can be selected according to the purpose. Carbon dioxide used in the present invention that is liquid at room temperature can be vaporized using a vaporizer before use.
[0071] In the present invention, the carbon dioxide gas concentration is not particularly limited, but is preferably 0.1% to 100%. If the carbon dioxide gas concentration is less than 0.1%, there is a risk that methane cannot be obtained sufficiently.
[0072] There are no particular limitations on the hydrogen used in the present invention, and the purity is also not particularly limited as long as it does not contain impurities such as sulfur that act as catalyst poisons, and the hydrogen can be selected according to the purpose.
[0073] In the present invention, the hydrogen gas concentration is not particularly limited, but is preferably 0.1% to 100%. If the hydrogen gas concentration is less than 0.1%, there is a risk that methane cannot be obtained sufficiently.
[0074] The methanation reaction of carbon dioxide can be expressed as CO2+4H2→CH4+2H2O. If the H2 / CO2 ratio is less than 1.0, the carbon deposition resistance (coking) decreases. If the H2 / CO2 ratio exceeds 5, a large amount of expensive hydrogen is used, which increases the cost and is not practical. The ratio is preferably 1.5 to 4.8, and more preferably 2.5 to 4.5.
[0075] The gas space velocity (GHSV) of the method for methanating a gas containing carbon dioxide gas and hydrogen gas using the methanation catalyst for methanating carbon dioxide according to the present invention is 500 to 8000 h -1 is preferred. GHSV is 500h -1If it is less than 10,000h, the amount of methane gas obtained per unit time may be small. -1 If the GHSV exceeds this limit, there is a risk that carbon dioxide will not be converted into methanation sufficiently. -1 is more preferable, and 2000 to 3000 hours -1 is more preferred.
[0076] The present inventors presume as follows why the methanation catalyst for methanating carbon dioxide according to the present invention is capable of methanating a gas containing carbon dioxide.
[0077] The methanation catalyst for methanating carbon dioxide according to the present invention can exhibit high crushing strength by generating a spinel phase containing magnesium, aluminum and nickel through high-temperature calcination, and therefore, even when used multiple times, the catalyst molded body can maintain high catalytic activity without bursting or powdering, and has excellent cycle characteristics (reusability).
[0078] In addition, because it contains highly dispersed fine particles of metallic nickel, it becomes active at lower temperatures than conventional methanation catalysts that methanate carbon dioxide, which also leads to power savings.
[0079] Furthermore, the methanation catalyst for methanating carbon dioxide according to the present invention contains a large amount of magnesium, and therefore has excellent resistance to sulfur poisoning, and has excellent catalytic activity in terms of durability as well.
[0080] The metallic nickel in the methanation catalyst for methanation of carbon dioxide according to the present invention is in the form of extremely fine particles, particularly fine particles of 1 to 50 nm, and is present throughout the catalyst particle, in the vicinity of the surface of the catalyst particle, or in the vicinity of the surface of the catalyst molded body. This increases the area in which the metallic nickel, which is an active metal species, comes into contact with carbon dioxide, and provides excellent catalytic activity even in a temperature range of 300°C or less.
[0081] The methanation catalyst for methanating carbon dioxide according to the present invention is prepared by calcining a precursor obtained by molding hydrotalcite, which is a layered double hydroxide, and therefore contains a large amount of fine pores, as the moisture in the hydrotalcite is dehydrated by high-temperature calcination. Therefore, the specific surface area and pore volume are very large. Furthermore, pores are formed by removing moisture and carbonate ions between the layers of the hydrotalcite during calcination, and the pore diameter can be reduced. Therefore, the methanation catalyst for methanating carbon dioxide according to the present invention can maintain a high specific surface area even when calcined at high temperatures, and can maintain a large BET specific surface area and pore volume, and can maintain catalytic activity for a long period of time.
[0082] The methanation catalyst for methanating carbon dioxide according to the present invention can support active metal species such as gold, silver, platinum, palladium, ruthenium, cobalt, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, and titanium, and can improve the catalytic activity and oxidation resistance. EXAMPLES
[0083] Examples of the present invention will be described below, but the present invention is not limited to these.
[0084] The crushing strength of the catalyst molded body was measured using a digital force gauge manufactured by IMADA in accordance with JIS Z8841 (granulated material - strength test method), and the average value was calculated from the measurements of 100 pieces to obtain the average crushing strength.
[0085] The pore volume was determined by the BJH method using a TriStar 3000 manufactured by Shimadzu Corporation.
[0086] The sizes of metallic nickel particles, ruthenium (Ru), and platinum (Pt) particles were measured from transmission electron microscope (JEM-F200, manufactured by JEOL Ltd.), and the average value of 360 or more primary particles was taken as the average particle diameter.
[0087] Identification of the hydrotalcite particles and evaluation of the morphology of Mg and Al in the methanation catalyst for methanating carbon dioxide were performed by X-ray diffraction measurement (X-ray diffractometer RINT-2500 (manufactured by Rigaku Corporation)). X-ray diffraction measurement was performed using the X-ray diffractometer at a diffraction angle 2θ of 3 to 80°.
[0088] The contents of magnesium, aluminum, and nickel in the methanation catalyst for methanating carbon dioxide were determined by dissolving the catalyst in acid and measuring the content by a plasma emission spectrometer SPS4000 (Seiko Denshi Kogyo Co., Ltd.).
[0089] The BET specific surface area was measured by the nitrogen BET method.
[0090] The carbon dioxide concentration was evaluated using a Shimadzu gas chromatograph GC2014.
[0091] Example 1 MgSO4·7H2O (261.99g) and Al2(SO4)3·8H2O (86.16g) were dissolved in water to make 1000ml. Separately, 1000ml of a solution in which Na2CO3 (100.49g) was dissolved in 14mol / L NaOH (235.4ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The mixed solution of magnesium salt and aluminum salt was added to this alkaline mixed solution and aged at 95℃ for 8 hours to obtain an alkaline suspension. The pH of the reaction solution at this time was 12.8.
[0092] Next, 500 ml of a mixed solution of magnesium salts, nickel salts, and aluminum salts containing MgSO4·7H2O (30.10 g), NiSO4·6H2O (60.01 g), and Al2(SO4)3·8H2O (120.20 g) was added to this alkaline suspension, the pH of the reaction solution was adjusted to 11.4, and it was further aged at 120°C for 4 hours to obtain hydrotalcite particles.
[0093] The obtained hydrotalcite particles (5400g) were mixed with boehmite (300g), PVA (3820g), water (300g) and propylene glycol (220g), and kneaded with a screw kneader. After kneading, the mixture was molded into a spherical shape with a diameter of 3mmφ, dried at 100°C, and then calcined in air at 800°C for 4 hours, and reduced at 700°C in an air stream containing hydrogen and argon gas for 1 hour to obtain a methanation catalyst for methanation of carbon dioxide. It was confirmed that the obtained methanation catalyst for methanation of carbon dioxide had a spinel structure, contained Mg and Al in the form of a composite oxide, and contained Ni in the form of a metal. The size of the obtained methanation catalyst for methanation of carbon dioxide was a sphere with a diameter of 3mmφ. The Ni / (Mg+Al+Ni) in the obtained catalyst was 0.158 (molar ratio).
[0094] Table 1 shows the composition (Mg, Al, Ni) contained in the catalyst, the average Ni particle size, the BET specific surface area, the average crushing strength, and the pore volume.
[0095] The catalytic activity of the methanation catalyst for methanating carbon dioxide was evaluated as the carbon dioxide conversion rate. For the evaluation, a stainless steel reaction tube with a diameter of 10 mm was filled with 10 to 30 g of the methanation catalyst for methanating carbon dioxide to create a catalyst tube. A mixed gas containing carbon dioxide gas (flow rate 100 ml / min) and hydrogen (flow rate 400 ml / min) as the raw gas was fed to this catalyst tube (reactor) at atmospheric pressure, reaction temperature 200°C to 300°C, and space velocity of 1000 h -1 After 10 minutes had elapsed and the temperature of the catalyst had stabilized, the inlet and outlet carbon dioxide gas concentrations were evaluated and the carbon dioxide conversion rate was calculated.
[0096] The carbon dioxide conversion rate (%) was calculated from the following formula. Carbon dioxide conversion rate (%) = ((inlet carbon dioxide gas concentration - outlet carbon dioxide gas concentration) / inlet carbon dioxide gas concentration) x 100
[0097] Table 2 shows the carbon dioxide conversion rate at reaction temperatures of 200° C., 250° C., and 300° C. The carbon dioxide conversion rate means the ratio of carbon dioxide in a gas containing hydrogen that is converted to methane.
[0098] <Example 2> Al2(SO4)3·8H2O (740.52g) and NiSO4·6H2O (15.34g) were dissolved in water to make 1500ml. Separately, 500ml of a solution in which Na2CO3 (12.60g) was dissolved in 14mol / L NaOH (475.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 55°C for 4 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 7.2.
[0099] The hydrotalcite particles obtained in the previous step were molded into spherical beads with a diameter of 4 mm in the same manner as in Example 1, and a methanation catalyst for methanating carbon dioxide was obtained in the same manner as in Example 1. The Ni / (Mg+Al+Ni) of the obtained catalyst was 0.154 (molar ratio).
[0100] <Example 3> MgSO4·7H2O (727.4g), Al(SO4)3·8H2O (80.15g), and NiSO4·6H2O (63.25g) were dissolved in pure water to make 1500ml. Separately, 500ml of a solution in which Na2CO3 (14.82g) was dissolved in 14mol / L NaOH (671.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150°C for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0101] The hydrotalcite particles obtained in the previous step were molded in the same manner as in Example 1 to form spherical beads with a diameter of 4 mm. The particles were calcined in air at 800°C for 8 hours to obtain a porous oxide powder, which was then reduced in an air stream containing hydrogen and argon gas at 950°C for 4.0 hours to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Mg+Al+Ni) ratio of the catalyst obtained here was 0.074 (molar ratio).
[0102] <Example 4> MgSO4·7H2O (33.1g), Al(SO4)3·8H2O (120.2g), and NiSO4·6H2O (60.01g) were dissolved in pure water to make 1500ml. Separately, 500ml of a solution in which Na2CO3 (14.82g) was dissolved in 14mol / L NaOH (671.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150°C for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0103] The hydrotalcite particles obtained here were molded into spherical beads with a diameter of 4 mm in the same manner as in Example 1. They were calcined in air at 800°C for 8 hours to obtain a porous oxide powder, which was then reduced in an air stream containing hydrogen and argon gas at 1100°C for 4.0 hours to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Mg+Al+Ni) ratio of the catalyst obtained here was 0.16 (molar ratio).
[0104] <Example 5> MgSO4·7H2O (33.1g), Al(SO4)3·8H2O (120.2g), and NiSO4·6H2O (60.01g) were dissolved in pure water to make 1500ml. Separately, 500ml of a solution in which Na2CO3 (14.82g) was dissolved in 14mol / L NaOH (671.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150°C for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0105] The hydrotalcite particles thus obtained were molded in the same manner as in Example 1 to form spherical beads having a diameter of 4 mm. The particles were calcined in air at 800°C for 4 hours to obtain a porous oxide powder. 100 g of the obtained spherical bead methanation catalyst for methanating carbon dioxide was spray-coated with 30 ml of a solution in which a Ru(NO3)3 solution (20 mL) having a Ru concentration of 10 g / L was dissolved in pure water, and after drying, reduction treatment was performed for 1.0 hour at 800°C in an air stream containing hydrogen and argon gas to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Mg+Al+Ni) ratio of the catalyst thus obtained was 0.16 (molar ratio), and the average particle diameters of the metallic Ni fine particles and metallic Ru fine particles were each 12 nm. The supported metal (Ru) content was 0.2 wt%.
[0106] <Example 6> MgSO4·7H2O (33.1g), Al(SO4)3·8H2O (120.2g), and NiSO4·6H2O (60.01g) were dissolved in pure water to make 1500ml. Separately, 500ml of a solution in which Na2CO3 (14.82g) was dissolved in 14mol / L NaOH (671.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150°C for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0107] The hydrotalcite particles obtained here were molded in the same manner as in Example 1 to form spherical beads with a diameter of 4 mm. The catalyst was calcined in air at 800°C for 4 hours to obtain a spherical methanation catalyst for methanating carbon dioxide. 30 ml of a solution in which K2(Pt(CN)4)·3H2O (0.42 g) was dissolved in pure water was sprayed onto 100 g of the obtained methanation catalyst for methanating carbon dioxide, and after drying, reduction treatment was performed for 1.0 hour at 800°C in an air stream containing hydrogen and argon gas to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Mg+Al+Ni) ratio of the catalyst obtained here was 0.16 (molar ratio), and the average particle diameters of the metallic Ni fine particles and metallic Pt particles were each 11 nm. The supported metal (Pt) content was 0.2 wt%.
[0108] <Comparative Example 1> 1080.0g of magnesium oxide powder and 110.3g of α-alumina powder were mixed and formed into 4mm spherical beads. The beads were baked at 1000℃ for 4 hours in air to obtain spherical carbon dioxide methanation catalyst. 100ml of a solution of Ni(NO3)2·6H2O (21.84g) dissolved in pure water was sprayed onto 100g of the obtained carbon dioxide methanation catalyst, which was then dried at 85℃ for 24 hours, and then reduced at 800℃ for 1.0 hour in an air stream containing hydrogen and argon gas to obtain a carbon dioxide methanation catalyst. The Ni / (Mg+Al+Ni) ratio of the obtained catalyst was 0.03 (molar ratio).
[0109] <Comparative Example 2> α-alumina powder was processed into 3 mm spherical beads. These were then calcined in air at 1000℃ for 4 hours. 100 ml of a solution of Ni(NO3)2·6H2O (58.50 g) dissolved in pure water was sprayed onto 100 g of the resulting spherical beads. After drying, the beads were reduced in an air stream containing hydrogen and argon gas at 800℃ for 1.0 hour to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Al+Ni) ratio of the catalyst obtained was 0.074 (molar ratio).
[0110] <Comparative Example 3> MgSO4·7H2O (100.21g), Al(SO4)3·8H2O (180.3g), and NiSO4·6H2O (2.33g) were dissolved in pure water to make 1500ml. Separately, 500ml of a solution in which Na2CO3 (14.82g) was dissolved in 14mol / L NaOH (671.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. The mixed solution of magnesium salt and aluminum salt was added to this alkaline mixed solution, and the mixture was aged at 150℃ for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 10.8.
[0111] The hydrotalcite particles thus obtained were molded in the same manner as in Example 1 to form spherical beads having a diameter of 4 mm. The particles were calcined in air at 800°C for 4 hours to obtain a porous oxide powder. 100 g of the obtained spherical bead methanation catalyst for methanating carbon dioxide was spray-coated with 30 ml of a solution in which RuCl3 (1.02 g) was dissolved in pure water, and after drying, reduction treatment was carried out at 800°C for 1.0 hour in an air stream containing hydrogen and argon gas to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Mg+Al+Ni) ratio of the catalyst thus obtained was 0.006 (molar ratio), and the average particle diameters of the metallic Ni fine particles and metallic Ru particles were each 10 nm. The supported metal (Ru) content was 0.2 wt%.
[0112] <Comparative Example 4> Al(SO4)3·8H2O (88.20g) and NiSO4·6H2O (380.55g) were dissolved in pure water to make 1500ml. Separately, 500ml of a solution of Na2CO3 (14.82g) dissolved in 14mol / L NaOH (671.0ml) was added to prepare an alkaline mixed solution with a total volume of 2000ml. 1000ml of an aqueous solution of MgSO4·7H2O (261.99g) and Al2(SO4)3·8H2O (86.16g) was added to this alkaline mixed solution, and the mixture was aged at 150℃ for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 11.1.
[0113] The hydrotalcite powder thus obtained was molded into spherical beads having a diameter of 4 mm in the same manner as in Example 1. The powder was calcined in air at 800°C for 2 hours to obtain a porous oxide powder, which was then subjected to a reduction treatment in an air stream containing hydrogen and argon gas at 800°C for 1.0 hour to obtain a methanation catalyst for methanating carbon dioxide. The Ni / (Mg+Al+Ni) ratio of the catalyst thus obtained was 0.574 (molar ratio).
[0114] [Table 1]
[0115] [Table 2]
[0116] In the methanation catalyst for methanating carbon dioxide according to the present invention, only nickel components are precipitated as fine metallic nickel from an oxide containing magnesium, aluminum, and nickel with a spinel structure, and nickel metal is contained on the surface and / or pore surface of the oxide containing magnesium and aluminum. The methanation catalyst for methanating carbon dioxide according to the present invention can convert carbon dioxide to methane with high efficiency even if the nickel content of the active metal species is as small as 1 to 30 wt%. Furthermore, the catalyst starts to show catalytic activity for methanating carbon dioxide from a reaction temperature of about 180°C, and shows a sufficient activity for methanating carbon dioxide, with a carbon dioxide conversion rate of about 55% to 92% at 250°C and a carbon dioxide conversion rate of about 75% to 92% at 300°C. In addition, the catalyst according to the present invention has high crushing strength, and shows the property of methanating carbon dioxide equivalent to that at the first use even when used repeatedly. It can also be used for coal gasification catalyst, ammonia decomposition catalyst, petroleum hardening catalyst, ethylene dimerization, asymmetric hydrogenation, hydrodesulfurization, cross-coupling, nylon raw material synthesis, etc. [Industrial Applicability]
[0117] The present invention relates to the methanation of carbon dioxide, and by using the present invention, methane can be efficiently obtained from carbon dioxide. The present invention can be widely applied to methane production technology, and will make a great contribution to the environmental field where carbon dioxide is treated, and the energy field where carbon dioxide is methanated to obtain methane.
Claims
1. A methanation catalyst for methanating carbon dioxide, comprising at least magnesium, aluminum and nickel, wherein the magnesium and aluminum are in the form of a composite oxide, the nickel is in the form of metallic nickel, and comprising 10 to 50 wt % magnesium, 5 to 35 wt % aluminum and 1 to 30 wt % nickel.
2. 2. The methanation catalyst for methanating carbon dioxide according to claim 1, wherein the average particle size of the metallic nickel in the catalyst is 1 to 50 nm.
3. 2. The methanation catalyst for methanating carbon dioxide according to claim 1, wherein the BET specific surface area of the catalyst is 5 to 100 m 2 / g of a methanation catalyst for methanating carbon dioxide.
4. 2. The methanation catalyst for methanating carbon dioxide according to claim 1, which contains one or more metals selected from gold, silver, platinum, palladium, ruthenium, cobalt, iron, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, and titanium, each having an average particle size of 50 nm or less.
5. 2. The methanation catalyst for methanating carbon dioxide according to claim 1, wherein the average crushing strength of the catalyst is 3 kgf / cm 2 The above methanation catalyst converts carbon dioxide into methanation.
6. A method for methanating carbon dioxide, using the methanation catalyst for methanating carbon dioxide according to claim 1.
7. A method for producing methane by reacting carbon dioxide in the presence of the methanation catalyst for methanating carbon dioxide according to claim 1.
8. 2. A method for producing a methanation catalyst for methanating carbon dioxide as described in claim 1, comprising the steps of producing hydrotalcite particles containing constituent elements as a precursor by a coprecipitation reaction, preparing a molded body, heating and sintering the molded body to form a porous catalyst body, and then heating and reducing the molded body.
Citation Information
Patent Citations
Co2 methanation catalyst and method for producing the same, and method for producing methane
JP2022094211A
Cited By
Method for preparing methanation catalyst for coal-based natural gas
CN120861059A
Preparation method of efficient nickel-magnesium-based catalyst for methanation of carbon dioxide
CN121244225A
A method for preparing a high-efficiency nickel-magnesium-based catalyst for carbon dioxide methanation
CN121244225B